Is CPAP the Key to Reduce the Cardiovascular Risk in Patients with OSA? - Abraham-Aggarwal, Kiran; Kacker, Ashutosh (International Archives of Otorhinolaryngology, 2025)
Introduction Obstructive sleep apnea (OSA) is a prevalent condition often managed with continuous positive airway pressure (CPAP) treatment. There is an ongoing debate about the link between OSA and cardiovascular disease (CVD), but the existing evidence points toward an association.Objective The present study aims to investigate whether CPAP is an effective strategy to reduce the risk of developing CVD risk among OSA patients.Methods The literature search was conducted in collaboration with Weill Cornell Medical College librarians, and we identified the five most recent papers highlighting the correlation between CPAP treatment for OSA and CVD risk reduction.Results Recent studies highlight the link between OSA and CVD, emphasizing the potential of the CPAP therapy to reduce the risks of developing CVD and the mortality associated with the condition. The analyses by Guo et al., Peker et al., Khan et al., and Wickwire et al., collectively involving thousands of patients across various study designs, including randomized clinical trials and retrospective cohort studies, consistently demonstrate that the CPAP treatment improves cardiovascular outcomes by lowering blood pressure, reducing sleepiness scores, and significantly decreasing the risk of serious CVD events, especially with consistent adherence to therapy.Conclusion Although further studies are needed to confirm these findings among patients with consistent high compliance to the CPAP treatment, it remains reasonable to continue to prescribe CPAP as the first-line therapy for OSA due to its potential cardiovascular benefits and low associated risks.
Keywords: otolaryngology; sleep apnea; cardiovascular disease; sleep medicine specialty; CPAP